2019
DOI: 10.3389/fchem.2018.00675
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Polymer Electrolyte Into Porous LiNi0.5Mn1.5O4 for High Performance All-Solid-State Microbatteries

Abstract: We report the electrodeposition of polymer electrolyte (PMMA-PEG) in porous lithium nickel manganese oxide (LiNi0.5Mn1.5O4) cathode layer by cyclic voltammetry. The cathode-electrolyte interface of the polymer-coated LNMO electrode has been characterized by scanning electron microscopy and electrochemical techniques. Electrochemical measurements consisting of galvanostatic cycling tests and electrochemical impedance spectroscopy revealed a significant improvement of the capacity values and the increase of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…The schematic representation of the mLB and the cross-sectional SEM images are displayed in Figure 50a. 582,588 With a prolonged number of CV cycles, it is observed that the electrodes are covered with a smooth layer of PE [ Figure 50 (b and c)]. However, for safety reasons, an additional thin PE layer is used apart from the electropolymerized PIS layer during the full cell fabrication.…”
Section: Microbattery Fabrication Using the In Situ Processmentioning
confidence: 99%
“…The schematic representation of the mLB and the cross-sectional SEM images are displayed in Figure 50a. 582,588 With a prolonged number of CV cycles, it is observed that the electrodes are covered with a smooth layer of PE [ Figure 50 (b and c)]. However, for safety reasons, an additional thin PE layer is used apart from the electropolymerized PIS layer during the full cell fabrication.…”
Section: Microbattery Fabrication Using the In Situ Processmentioning
confidence: 99%
“…This is due to the filling of polymer over the porous of LNMO, that increases its working efficiency. Therefore, in this paper they have successfully fabricated a microbatteries by LNMO as a cathode, polymer as a electrolyte and TiO 2 nanotube as a anode 20 . Innovative multi functioning shoes were developed and discussed in this paper.…”
Section: Improvement Of Sensing Performance Including the Temperaturementioning
confidence: 99%
“…In order to achieve practical implementation of 3DMBs, rapid, scalable and cost‐effective manufacturing techniques for fabricating microelectrodes are essential. Various microfabrication strategies have been developed, including semiconductor‐processing technologies, [6] photolithography, [45,46] electrochemical deposition, [19–21,47,48] plasma etching, [49,50] mask‐assisted filtration, [51] microinjection [52] , laser‐scribing [53] and ‐ablation techniques [54–56] …”
Section: Electrochemically‐active Materials and Cost‐effective Methodmentioning
confidence: 99%
“…Taken with permission from Wiley (2019), Reference [12]. Review tor-processing technologies, [6] photolithography, [45,46] electrochemical deposition, [19][20][21]47,48] plasma etching, [49,50] mask-assisted filtration, [51] microinjection [52] , laser-scribing [53] and -ablation techniques. [54][55][56] Recent printing technologies, such as fused-filament fabrication, FFF (or termed as fused-deposition modeling (FDM)), [25,[57][58][59][60] inkjet, spray and screen printing [61][62][63] hold many opportunities for the mass production of microbatteries.…”
Section: Electrochemically-active Materials and Cost-effective Methodmentioning
confidence: 99%